The Effectiveness of Pregnancy Online Classes (PROCLASS) on the Level of Knowledge and Anxiety Ahead of Labor During the COVID-19 Pandemic - Sari, Marlynda Happy Nurmalita; Anggraini, Dina Dewi; Kusumawati, Yuli (Poltekkes Kemenkes Surakarta, 2023)
Background: Restrictions on health services such as prenatal checks and the Pregnant Women Class program during the COVID-19 pandemic in several regions will have an impact on the quality of services for pregnant women. Purpose: Pregnancy online classes can potentially increase knowledge and reduce anxiety ahead of labor during the COVID-19 pandemic. Methods: Quasi-experimental and nonequivalent control group, pretest and posttest design approach Each group of 30 people (purposive sampling technique). Pre-test and PROCLASS provide material every week through videos uploaded to the WhatsApp group. The instrument uses a questionnaire (Google Form). Independent t-test and Mann-Whitney test to compare the PROCLASS and control groups. Dependent t-test and Wilcoxon test to compare the pre-and post-test in the PROCLASS group. Results: There were differences in the pre-post test on the variables of knowledge and anxiety in the PROCLASS group, respectively (p-value 0.000). There was a difference in knowledge between the PROCLASS and control groups (p-value 0.002), with an average knowledge of 88.83 in the PROCLASS group and 85.73 in the control group. There were also differences in anxiety levels between the PROCLASS and control groups (p-value 0.000), with an average anxiety level of 28.17 in the PROCLASS group and 45.70 in the control group. Conclusion: PROCLASS has proven effective in increasing knowledge and reducing the anxiety level of pregnant women before giving birth during the COVID-19 pandemic so that health workers can carry out the process (Puskesmas).